KAJIAN STUDI KULTURAL DAN PEDAGOGIK DALAM PENDIDIKAN INDONESIA - Walan Yudhiani (UIN Sumatera Utara Medan, 2014)
Education and freedom are a cultural studies, how the regim or goverment conservate culture througt education institution. When a regime presses its willness and takeover individual freedom and their culture that means education to be oppressive tools for individu and sociaty group.